The issue of sustainable urban development in a neoliberal age. Discursive entanglements and disputes - Skrede, Joar (FormAkademisk, 2013)
The city of Oslo, the Norwegian capital, is in the midst of executing a huge urban waterfront project in Bjørvika. This project has triggered several years of public debate. A key concept in the development project is “sustainable development”, but it is unclear what the concept implies. Several interests are involved which emphasise different goals and different values. In this article, a discourse analysis of the concept, in this particular context, is conducted. Five discourses are identified, which overlap as well as collide. Special attention is paid to how the respective discourses are related to a neoliberal form of government, and as part of the analysis, a discussion of how cultural heritage is used to increase the city’s attractiveness is undertaken. This article concludes that planning for a sustainable use of cultural heritage should imply establishing a reflective cultural policy not subsumed under economic sustainability.